Copyright and information privacy : conflicting rights in balance - Giovanella, Federica (Cheltenham, UK : Edward Elgar Publishing, 2017)
Federica Giovanella examines the on-going conflict between copyright and informational privacy rights within the judicial system in this timely and intriguing book. Adopting a comparative approach focusing on the United States, Canada and Italy, Dr Giovanella skilfully explores the strategies through which judges solve conflicts between Internet users' data protection and copyright holders' enforceable rights. Using research centred on a selection of lawsuits in which copyright holders attempted to enforce their rights against Internet users suspected of illegal file-sharing, this book analyses the cases and regulatory frameworks concerning both privacy and copyright. Copyright and Information Privacy demonstrates that these decisions were ultimately the by-products of different policy conceptions of the two conflicting rights. Whilst providing a comprehensive analysis of the conflict between copyright and data protection, this book also stimulates the debate surrounding the role that judges have in balancing conflicting rights, and examines their reasoning in resolving such conflict, taking into consideration the process of conceptual balancing. Perceptive and contemporary in topic, this book will be beneficial to both scholars and students of intellectual property, privacy and comparative law. Federica Giovanella examines the on-going conflict between copyright and informational privacy rights within the judicial system in this timely and intriguing book. Adopting a comparative approach focusing on the United States, Canada and Italy, Dr Giovanella skilfully explores the strategies through which judges solve conflicts between Internet users' data protection and copyright holders' enforceable rights. Using research centred on a selection of lawsuits in which copyright holders attempted to enforce their rights against Internet users suspected of illegal file-sharing, this book analyses the cases and regulatory frameworks concerning both privacy and copyright. Copyright and Information Privacy demonstrates that these decisions were ultimately the by-products of different policy conceptions of the two conflicting rights. Whilst providing a comprehensive analysis of the conflict between copyright and data protection, this book also stimulates the debate surrounding the role that judges have in balancing conflicting rights, and examines their reasoning in resolving such conflict, taking into consideration the process of conceptual balancing. Perceptive and contemporary in topic, this book will be beneficial to both scholars and students of intellectual property, privacy and comparative law.--Provided by publisher.
1. The thorny issue of balancing rights -- 2. Copyright and file-sharing regulation in the US, Canada and Italy -- 3. Personal data protection legislation -- 4. Copyright vs. data protection : case studies -- 5. Conclusions : conceptual balancing
Includes bibliographical references (pages 316-347) and index.
Keywords: Conflict of laws -- Copyright -- Canada; Conflict of laws -- Copyright -- Italy; Conflict of laws -- Privacy, Right of -- United States; Conflict of laws -- Privacy, Right of -- Canada; Conflict of laws -- Privacy, Right of -- Italy